Sport as a tool for public diplomacy in Hungary - Garamvölgyi, B.; Dóczi, T. (Physical Culture and Sport. Studies and Research, 2021)
Sport is often utilized as a tool by governments and nation-states in building a favorable international image, seeking external political legitimacy, and strengthening nation-building endeavors across borders. Given its universal appeal, sport is often perceived as a valuable soft power asset for conveying positive messages to foreign publics. Against this backdrop, the present study aims to introduce the sports diplomacy approach of Hungary, specifically focusing on the sta-te-led utilization of sport in public diplomacy under the recent government of Viktor Orbán (2010-2020). With the insti-tutionalization of sport in public diplomacy, Hungary has become a pioneering country in Central and Eastern Europe that can provide an example for other nation-states in the region. The Hungarian government`s sports diplomacy ambitions have not been curbed by the COVID-19 pandemic, and the country continues to invest large amounts of public funding in attracting and organizing international sporting competitions. Hosting the Summer Olympic Games in Budapest remains the ultimate goal of the current government`s sports diplomacy strategy, which focuses on elite sport.